A COMUNICAÇÃO NO MOVIMENTO WESLEYANO: PISTAS PARA UMA MÍDIA METODISTA HOJE - Plaça, Joyce Torres (2010)
In eighteenth s century England, John Wesley employed the media in all aspects of the articulation of the Methodist movement, in benefit of the mission of reforming both the nation and the church. However, in the third millennium s Brazil, the evangelic groups communication does not stand up to the Christian ideal, circumscribing itself to the gospel culture of the society of the spectacle . By means of the theological and historical inquiry of Christian communication, starting with the advent of the printing press, and of the Wesleyan heritage, based on a communicational perspective, together in dialogue with relevant authors for the transition to the twentieth-first century, according to the new technological order that introduced in the global community a virtual reality, our objective is to identify non-negotiable practices for a religious media that incarnates the public vocation of Methodism today.